Automated Rainout Shelter's Design for Well‐Defined Water Stress Field Phenotyping of Crop Plants. Issue 1 (26th October 2016) - Kant, Surya; Thoday‐Kennedy, Emily; Joshi, Sameer; Vakani, Jignesh; Hughes, Jess; Maphosa, Lancelot; Sadler, Andy; Menidis, Meri; Slater, Anthony; Spangenberg, German
Abstract : Field phenotyping to identify water stress‐tolerant crop genotypes is challenging due to uncertainty in the timing of rainfall. Rainout shelters offer a way of establishing controlled water stress environments by excluding untimely rain events. Here, we present a detailed description of custom‐designed rainout shelters. These shelters are fully automated and portable. The rainout shelters were constructed from steel arch frames and polyethylene cladding, which move on plastic road barriers. The three connected shelters, each 20 × 10 m, are rain sensor activated, solar powered and equipped with a motion sensor camera for remote monitoring. These rainout shelters have proven to be effective tools for field water stress phenotyping.